Introduction to money laundering deterrence - Cox, Dennis (John Wiley & Sons, 2011)
Every criminal act anywhere that involves obtaining money illegally produces funds which need to be laundered. The IMF estimates that 2-5 of global GDP ($590bn and $1. 5 trillion) is laundered every year - $590bn is the equivalent of Spain's yearly output